P.213 Long-Term Improvement Of Gait And Cognition After Primary Endoscopic Third Ventriculostomy (ETV) In Adult Obstructive Hydrocephalus. (November 2021) - Salterio, N; Zwimpfer, TJ; Holubkov, R; Katzen, H; Luciano, MG; Jensen, H; Nagel, SJ; Williams, MA; Hamilton, MG
Abstract : Background: Adults with obstructive hydrocephalus often present with cognitive and/or gait dysfunction in addition to symptoms of raised ICP. We previously reported improvement of cognitive and gait function 3 months following primary adult ETV. This abstract presents long-term results in this group. Methods: Obstructive hydrocephalus was identified based on tri-ventriculomegaly on CT and/or MRI. Gait velocity (10 m timed gait) and cognitive function (Montreal Cognitive Assessment [MoCA]) were measured at two timepoints: pre-ETV and ≥9 months post-ETV. Results: Sixteen adults underwent primary ETV and completed a long-term assessment. Mean age was 60 years and 10 (63%) were male. Etiology: 10 (62.5%) congenital and 6 (37.5%) acquired. Mean long-term follow-up time for cognitive and gait assessments was 14.4 and 13.7 months, respectively. The long-term MoCA within patient median change was +2 points (n= 15; p = 0.007). Group medians were 23/30 (pre-ETV) and 26/30 (post-ETV). The long-term gait velocity within patient median change was +0.4 m/s (n= 12; p < 0.001). Group medians were 0.7 m/s (pre-ETV) and 1.3 m/s (post-ETV). Conclusions: ETV in adults with obstructive hydrocephalus results in long-term improvement of cognition and gait velocity when assessed ≥9 months post-ETV. Larger cohorts will determine the generalizability of these results. Hydrocephalus Association supported project.